La mise en scène de l'écrivain comme sacrifié dans la littérature du premier romantisme allemand : une nouvelle forme de sacrifice ?. Novalis et la mise en scène de l’écrivain à la lumière des théories de René Girard - Tessier Amorim, Hélène (Carnets, 2018)
Jena Romanticism can be used as an example to illustrate the conscious and unconscious permanency and transmission of sacrifice, and this despite Christ’s revelation of the mechanism, as Wackenroder, Tieck and Novalis offer us a new and original staging of the writer. The redefinition of the poet and of the act of creation around 1800 allows a reconciliation between mimetic theory and writing. In their self-reflexive novels, the sacrifice takes a new form, when these writers must find in the resumption of sacrifice an adequate form between travesty and nothingness, allowing the reappropriation of the dynamics of sacrifice, but also, at the end, writing, literary production.